2000
DOI: 10.1063/1.1287756
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of mechanical properties for dense and porous polymer films having a low dielectric constant

Abstract: Governing factors in stress response of nanoparticle films on water surface J. Appl. Phys. 110, 102218 (2011) Nanomechanical properties of sputter-deposited HfO2 and HfxSi1-xO2 thin films J. Appl. Phys. 110, 043527 (2011) Effect of epitaxial strain on the cation distribution in spinel ferrites CoFe2O4 and NiFe2O4: A density functional theory study Appl. Phys. Lett. 99, 081916 (2011) Direct measurement of intrinsic critical strain and internal strain in barrier films J. Appl. Phys. 110, 044907 (2011) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A second explanation for the observed modulus increase may be the reversible compression of the porous membrane under the AFM tip during indentation. Compression of the basement membrane would result in a higher density of membrane fibers and “crosslinks”, which may in turn cause an increase in the modulus (Xu et al, 2000). Similarly, a local, permanent, change in the membrane structure may occur upon indentation (strain hardening), creating an increased membrane density and subsequent increase in elastic modulus.…”
Section: Discussionmentioning
confidence: 99%
“…A second explanation for the observed modulus increase may be the reversible compression of the porous membrane under the AFM tip during indentation. Compression of the basement membrane would result in a higher density of membrane fibers and “crosslinks”, which may in turn cause an increase in the modulus (Xu et al, 2000). Similarly, a local, permanent, change in the membrane structure may occur upon indentation (strain hardening), creating an increased membrane density and subsequent increase in elastic modulus.…”
Section: Discussionmentioning
confidence: 99%
“…minimum UV-exposure time required for the stable SHIO was 2 h. The elastic modulus of the silk hydrogel film was increased (more rigid), along with the reduced elastic deformation range, when the UV-exposure time increased. And, we observed that the elastic modulus of the SHIO was smaller than that of the bulk silk hydrogel film due to porosity of the SHIO (more elastic) (27). The elastic deformation range of the SHIO was 10%, similar to bulk, and the optical response was significantly weakened at strains greater than the elastic range (Fig.…”
mentioning
confidence: 75%
“…23,24 The elastic modulus and initial stress measured from these three methods are in good agreement. 25 For the dense film samples, a Young's modulus of 3.9 GPa was obtained independently from both the bulge test and nanoindentation methods. The initial stress of 35 MPa and 16 MPa for the dense and porous film samples, respectively, was also obtained from both the bulge test and single-substrate bending beam methods.…”
Section: Measurement Of Mechanical Propertiesmentioning
confidence: 99%